Insulin B-chain hybrid peptides are agonists for T cells reactive to insulin B:9-23 in autoimmune diabetes - Wenzlau, Janet M.; DiLisio, James E.; Barbour, Gene; Dang, Mylinh; Hohenstein, Anita C.; Nakayama, Maki; Delong, Thomas; Baker, Rocky L.; Haskins, Kathryn (Frontiers in Immunology, 2022)
Insulin is considered to be a key antigenic target of T cells in Type 1 Diabetes (T1D) and autoimmune diabetes in the NOD mouse with particular focus on the B-chain amino acid sequence B:9-23 as the primary epitope. Our lab previously discovered that hybrid insulin peptides (HIPs), comprised of insulin C-peptide fragments fused to other -cell granule peptides, are ligands for several pathogenic CD4 T cell clones derived from NOD mice and for autoreactive CD4 T cells from T1D patients. A subset of CD4 T cell clones from our panel react to insulin and B:9-23 but only at high concentrations of antigen. We hypothesized that HIPs might also be formed from insulin B-chain sequences covalently bound to other endogenously cleaved ß-cell proteins. We report here on the identification of a B-chain HIP, termed the 6.3HIP, containing a fragment of B:9-23 joined to an endogenously processed peptide of ProSAAS, as a strong neo-epitope for the insulin-reactive CD4 T cell clone BDC-6.3. Using an I-Ag7 tetramer loaded with the 6.3HIP, we demonstrate that T cells reactive to this B-chain HIP can be readily detected in NOD mouse islet infiltrates. This work suggests that some portion of autoreactive T cells stimulated by insulin B:9-23 may be responding to B-chain HIPs as peptide ligands.